Matematyka
 
Brak innych książek z tego przedmiotu
 
Autorzy: Joanna Czarnowska, Jolanta Wesołowska, Wojciech Babiański, Lech Chańko
Wydawnictwo: Nowa Era
Rok wydania: 2014
Rozwiąż równanie 4.8 gwiazdek na podstawie 5 opinii

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

`[3(1-2x)-2(3x-1)]*[3(1-2x)+2(3x-1)]=1`  

`[3-6x-6x+2]*[3-6x+6x-2]=1`  

`(5-12x)*1=1`  

`5-12x=1\ \ \ |-5`  

`-12x=-4\ \ \ |:(-12)`  

`x=4/12=1/3`  

 

 

`d)`  

`(3x-2)(3x+2)=9(x-1/3)^2`  

`(3x)^2-2^2=9(x^2-2*x*1/3+(1/3)^2)`  

`9x^2-4=9(x^2-2/3x+1/9)`  

`9x^2-4=9x^2-6x+1\ \ \ |-9x^2`  

`-4=-6x+1\ \ \ |+6x`  

`6x-4=1\ \ \ |+4`  

`6x=5\ \ \ |:6`  

`x=5/6`